Від планування до звітності, або які програмні додатки краще використовувати в проектному менеджменті - Лук’янова, К. Ю. (ХНУРЕ, 2019)
The given work is devoted to the analysis of modern project management applications that optimize planning, monitoring and control processes in information technology and software products development. A Gantt chart, Product Breakdown Structure and Work Breakdown Structure are standard techniques used in project planning that can be automated. In this abstract, we have compiled a list of extremely effective team management and project planning tools, that can help to optimize process to plan essential project milestones, and that you can adopt today and be more efficient in project planning and team coordination.